Zero-emission hardness removal process for aluminum-based adsorption material
By preparing aluminum-based adsorbent materials and regenerating them with carbon dioxide, the problem of waste liquid being difficult to discharge zero in traditional water body hardness removal methods is solved, and an efficient and environmentally friendly water body hardness removal effect is achieved.
Patent Information
- Application Number
- CN202510037966.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2045-01-10
AI Technical Summary
Traditional water body hardness removal methods are often accompanied by a large amount of waste liquid, making it difficult to achieve zero emissions, and may introduce new pollutants, increasing the difficulty and cost of subsequent treatment.
By controlling the aluminum ion concentration and adding low-concentration dispersant, aluminum-based adsorbent materials are prepared, and the adsorbent materials are regenerated with low-concentration carbon dioxide to achieve zero emission of wastewater.
The zero-emission effect of water body hardness removal is achieved. The hardness ions in the wastewater are separated in the form of carbonate precipitation, and carbon dioxide is fixed, reducing the treatment cost.
Smart Images

Figure CN119461576A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of water treatment, and in particular is a zero-discharge hardness removal process of aluminum-based adsorption materials. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Traditional methods for removing water hardness often use chemical agents, such as lime softening and dosing treatment. These methods often produce a large amount of waste liquid while removing hardness, making it difficult to achieve true zero discharge. In addition, the use of chemical agents may also introduce new pollutants, increasing the difficulty and cost of subsequent treatment.
[0004] Some studies have used aluminum ion modified resin to remove hardness ions in water, using its hydrolysis and polymerization characteristics to produce hydroxide or bimetallic oxides to increase the removal capacity of ion exchange resin for hardness ions. However, the above method requires the introduction of strong acid to regenerate the resin, and the regeneration method is complicated and has great environmental hazards.
[0005] Therefore, there is an urgent need to develop an environmentally friendly, efficient, and zero-emission water hardness removal process. Summary of the invention
[0006] In order to solve the above problems, the present invention provides a zero-emission hardness removal process for aluminum-based adsorbent materials. The present invention prepares an aluminum-based adsorbent material by controlling the aluminum ion concentration and adding a low concentration of dispersant. During the ion exchange process of the adsorbent material, the particle size of the aluminum hydroxide precipitate generated is between 5nm and 70nm and attached to the adsorbent material skeleton, so that the adsorbent material can be regenerated by low concentration of carbon dioxide, and the regeneration efficiency reaches more than 90%, thereby achieving zero emission of wastewater.
[0007] In order to achieve the above object, the present invention adopts the following technical solution: The present invention provides a zero-emission hardness removal process for aluminum-based adsorption materials, comprising: Mixing the sodium salt and the aluminum salt uniformly in the solution to obtain a mixed solution; The mixed solution is used to perform ion exchange with a cation exchange resin to obtain an aluminum-based adsorption material; The aluminum-based adsorption material is used to treat water, adsorb calcium ions or magnesium ions, form nano-scale aluminum hydroxide precipitates and attach to the aluminum-based adsorption material skeleton, and collect water; Carbon dioxide gas is used to regenerate the aluminum-based adsorption material to dissolve the nano-scale aluminum hydroxide precipitate and replace calcium bicarbonate or magnesium bicarbonate. Water is collected and allowed to stand to form calcium carbonate or magnesium carbonate precipitate.
[0008] When the aluminum-based adsorbent prepared by the present invention treats water containing hardness ions (such as calcium ions and magnesium ions), the hardness ions replace the aluminum ions from the exchange sites, forming nano-scale aluminum hydroxide precipitation and attaching to the adsorbent material skeleton. At the same time, based on the principle of electrical neutrality, when each equivalent of hardness ions is removed, an equivalent of alkalinity ions (such as hydroxide, bicarbonate, carbonate, etc.) are also removed. Taking calcium ions as an example, the specific reaction process is as follows: ; ; ; The overall reaction is: ; When the aluminum-based adsorbent material completely adsorbs the hardness ions, it no longer has the ability to remove hardness, and the adsorbent material needs to be regenerated. The regeneration method is as follows.
[0009] (1) Introduce carbon dioxide (CO2) gas to produce carbonic acid: ; (2) Carbonic acid dissociates to form protons: ; (3) The protons formed can dissolve the aluminum hydroxide precipitated on the skeleton of the adsorbent material and release aluminum ions: ; (4) Low concentrations of aluminum ions utilize the high selectivity of the adsorption material to exchange the hardness ions at the site: ; (5) The formed calcium bicarbonate solution forms calcium carbonate precipitation after leaving the acidic environment of the adsorption material: .
[0010] The present invention has found that during the ion exchange process, if the particle size of aluminum hydroxide precipitation is between 5nm and 70nm, it can be attached to the skeleton of the adsorbent material and can be regenerated by carbon dioxide. Therefore, when the aluminum ions are loaded, the present invention uses a dispersant (such as sodium chloride, sodium polyacrylate, sodium hexametaphosphate, etc.) to first occupy the ion exchange sites of part of the resin, and disperse the distribution of aluminum ions on the resin. In the subsequent water treatment process, sodium ions are ion exchanged with calcium ions or magnesium ions, but they cannot be regenerated by CO2. At the same time, due to the low sodium ion content, the overall treatment performance of the resin is not greatly affected. Therefore, preferably, the mass concentration of the sodium salt is 0.002%-0.005% to obtain the expected dispersion effect and ensure the water treatment performance of the resin.
[0011] In order to obtain a better dispersion effect, the present invention also studies the types of sodium salts. Preferably, the sodium salt is sodium chloride, sodium polyacrylate or sodium hexametaphosphate.
[0012] The concentration of the aluminum salt solution is also an important factor affecting the dispersibility of aluminum ions. Therefore, the present invention studies the concentration of the aluminum salt. Preferably, the mass concentration of the aluminum salt solution is 0.1%-3.0%.
[0013] In order to obtain a better dispersion effect, the present invention also studies the types of aluminum salts. Preferably, the aluminum salt is aluminum chloride.
[0014] In order to ensure the ion exchange efficiency of sodium ions, aluminum ions and resin, the present invention studies the solid-liquid ratio of the cation exchange resin and the mixed solution. Preferably, the solid-liquid ratio of the cation exchange resin to the aluminum salt solution is 1:50-60.
[0015] In order to allow sodium ions and aluminum ions to effectively occupy the ion exchange sites of the resin, the present invention studies the contact time between the two. Preferably, the contact time between the mixed solution and the cation exchange resin is 10 min-15 min.
[0016] The cation exchange resin can perform ion exchange with sodium salt and aluminum salt and remove hardness ions. In order to obtain a better hardness removal effect, the present invention studies the types of cation resins. Preferably, the cation exchange resin is a strongly acidic cation exchange resin.
[0017] Different from the traditional method, the nano-scale aluminum hydroxide precipitate of the present invention can be attached to the skeleton of the ion exchange resin and can be regenerated by CO2. Therefore, the particle size of the nano-scale aluminum hydroxide precipitate is studied in the present invention. Preferably, the particle size of the nano-scale aluminum hydroxide precipitate is 2nm-70nm.
[0018] The partial pressure of carbon dioxide will affect the regeneration efficiency. Therefore, the partial pressure of carbon dioxide is optimized in the present invention. Preferably, the partial pressure of carbon dioxide is 1.5Kg-10Kg.
[0019] In summary, the hardness removal process of the present invention does not use any chemical agents, but only utilizes carbon dioxide gas. The regeneration process does not produce waste liquid, and the hardness ions removed from the water body are separated in the form of precipitation, truly achieving the effect of zero emission. During the entire hardness removal process, the hardness ions are finally separated from the influent water in the form of carbonate precipitation, and the fixation of carbon dioxide and the removal of hardness ions are achieved at the same time.
[0020] Beneficial Effects of the Invention (1) The hardness removal process of the present invention does not use any chemical agents, and only uses carbon dioxide gas as a regeneration agent. The regeneration process does not produce waste liquid, and the hardness ions are finally separated from the influent water in the form of carbonate precipitation. At the same time, the fixation of carbon dioxide and the removal of hardness ions are achieved, achieving the requirement of zero emission.
[0021] (2) The aluminum-based adsorption material of the present invention is still structurally stable at 50°C and maintains its hardness removal performance, and is suitable for in-situ hardness removal processes of high-temperature water bodies such as boiler wastewater and circulating cooling water.
[0022] (3) The process of the present invention is simple, easy to operate, low in cost, and easy to promote and apply. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention, and the exemplary embodiments of the present invention and their description are used to explain the present invention and do not constitute improper limitations on the present invention.
[0024] Figure 1 It is a schematic diagram of the exchange between aluminum-based adsorbent material and calcium ions; Figure 2 This is a schematic diagram of the formation of nano-scale aluminum hydroxide precipitation by aluminum ions during the ion exchange process; Figure 3 It is a schematic diagram of the precipitation reaction of carbon dioxide and nano-aluminum hydroxide; Figure 4 is a schematic diagram of a carbon dioxide-regenerated aluminum-based adsorbent material; Figure 5 is a graph showing changes in calcium ion concentration during the treatment of the aluminum-based adsorption material in Example 1; Figure 6 This is a graph showing changes in calcium ion concentration during the second water production experiment of the aluminum-based adsorption material in Example 1; Figure 7 is a graph showing changes in calcium ion concentration during the treatment of the aluminum-based adsorption material in Example 2; Figure 8 This is a graph showing changes in calcium ion concentration during the second water production experiment of the aluminum-based adsorption material in Example 2; Fig. 9 This is a graph showing changes in calcium ion concentration during the treatment of the aluminum-based adsorption material in Example 3. DETAILED DESCRIPTION
[0025] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0026] The present invention will be further described in detail below in conjunction with specific embodiments. It should be noted that the specific embodiments are intended to explain the present invention rather than to limit it.
[0027] Example 1 In order to meet the discharge standards for mining wastewater, the actual wastewater from a mine in Shandong was treated, and the water quality is as follows: Table 1 Wastewater index of a mine in Shandong
[0028] The present invention is directed to the following examples of water hardness removal: The preparation of aluminum-based adsorption materials includes: (1) Sodium chloride and aluminum chloride are added to water in sequence and mixed evenly to obtain a mixed solution, wherein the mass concentration of sodium chloride is 0.002% and the mass concentration of aluminum chloride is 1%.
[0029] (2) Aluminum salt modification: The cation exchange resin is mixed with the mixed solution prepared in step (1) at a solid-liquid ratio of 1:50, and adsorption is performed under stirring for 10 minutes to obtain an aluminum-based adsorption material; (3) Water treatment: 50 mL of the aluminum-based adsorbent material prepared in step (2) was filled into a plexiglass column with an inner diameter of 15 mm to form a resin column. The mining wastewater was passed through the plexiglass column from top to bottom at a flow rate of 5 mL / min. The treated water samples were collected at the lower outlet of the plexiglass column and their hardness was tested. The obtained calcium ion concentration was recorded as a function of the number of operating beds. Figure 5 shown.
[0030] from Figure 5 It can be seen that in the first 60 beds of the aluminum-based adsorption material, the calcium ion concentration of the treated water is always zero, until the 70th bed is run, the material begins to penetrate, and the calcium ion concentration in the effluent rises to about 10 mg / L. Then, when it runs to the 100th bed, the aluminum-based adsorption material is basically penetrated.
[0031] (4) Regeneration: Use carbon dioxide gas for regeneration, connect the carbon dioxide gas cylinder to the resin column, and adjust the carbon dioxide pressure to 2kg. After regeneration for 60 minutes, release the carbon dioxide pressure and drain the water in the column. After the discharged liquid is left to stand for 20 minutes, a white calcium carbonate precipitate is formed. The test results show that the calcium ion concentration in the discharged liquid is 500mg / L. The mass of the separated calcium carbonate solid after drying is 10.75g. Based on this calculation, the regeneration efficiency is about 95%.
[0032] After regeneration is completed, a second water production experiment is carried out to verify the regeneration effect and the hardness removal effect after regeneration. Figure 6 shown.
[0033] from Figure 6 It can be seen that in the first ten beds of the second water production, the calcium ion concentration was about 30 mg / L, and then decreased to 0 mg / L. Therefore, if the hardness needs to be completely removed, the process needs to flush 5-10 beds after regeneration to clean the residual solution in the reactor.
[0034] Embodiment 2: The influent water was taken from a coal mine wastewater in Shandong. Compared with Example 1, the calcium ion concentration of the coal mine wastewater was lower, about 300 mg / L.
[0035] The preparation of aluminum-based adsorption materials includes: (1) Sodium chloride and aluminum chloride are added to water in sequence and mixed evenly to obtain a mixed solution, wherein the mass concentration of sodium chloride is 0.005% and the mass concentration of aluminum chloride is 3%.
[0036] (2) Aluminum salt modification: The cation exchange resin is mixed with the mixed solution prepared in step (1) at a solid-liquid ratio of 1:60, and adsorption is performed under stirring for 15 minutes to obtain an aluminum-based adsorption material; (3) Water treatment: 20 mL of the aluminum-based adsorbent material prepared in step (1) was loaded into a plexiglass column with an inner diameter of 7 mm to form a resin column. During operation, the inlet flow rate of the actual wastewater sample was 10 mL / min, and 5 mL of effluent water sample was taken out for calcium ion concentration detection after every 20 beds were treated.
[0037] like Figure 7 As shown in the experimental results, it was found that in the first 140 beds of operation, the effluent calcium ion concentration was 0 mg / L, it began to penetrate when the bed length reached 160, and it was basically completely penetrated when the bed length reached 240.
[0038] (4) Regeneration: The penetrated aluminum-based adsorbent material is regenerated with carbon dioxide. The resin column is connected to a carbon dioxide cylinder, and the carbon dioxide pressure is adjusted to 5 kg and maintained at this pressure for 60 minutes. After the regeneration is completed, the liquid in the organic glass column is drained. After standing for 20 minutes, a large amount of white calcium carbonate precipitate is produced. The white precipitate is separated, dried and weighed, and the concentration of calcium ions in the liquid phase is tested. The test results show that the calcium ion concentration in the liquid phase is 450 mg / L, and the obtained white precipitate weighs 2.7 grams. It can be seen that the regeneration efficiency is about 98%.
[0039] After regeneration, the operating parameters and influent water quality were kept unchanged, and a second water production experiment was conducted to verify the regeneration effect of the process. Figure 8 shown.
[0040] The experimental results show that the treatment effect after regeneration is only slightly lower than the first time. The effluent calcium ion concentration is about 5 mg / L when treating 140 beds, and the adsorption material is completely penetrated when running 240 beds, which can meet the specific emission and reuse requirements.
[0041] Example 3 A solution for removing the hardness of boiler circulating water at 50°C. The aluminum-based adsorption material prepared in Example 2 is used to directly achieve in-situ hardness removal inside the boiler system pipeline. Among them, the circulating water hardness is 300mg / L. The method uses 15mL of aluminum-based adsorption material, which is loaded into a plexiglass column with an inner diameter of 7mm to form a resin column. Boiler circulating water at 50°C is passed at a flow rate of 5mL / min to verify the stability of the aluminum-based adsorption material at high temperatures and the hardness removal effect.
[0042] Removal effect Fig. 9 As shown, when the inlet water is 50°C, the aluminum-based adsorption material still maintains its structural stability and its hardness removal effect at room temperature. After running 140 beds, the outlet water hardness is still close to 0 mg / L.
[0043] The carbon dioxide regeneration and the second water production experiment were carried out in the same manner as in Example 2. The results showed that the treatment effect of the regenerated aluminum-based adsorption material was consistent with that of the original aluminum-based adsorption material.
[0044] This experiment proves that aluminum-based adsorption materials can be used for hot water treatment at 50°C.
[0045] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A zero-emission hardness removal process for aluminum-based adsorption materials, characterized in that: include: Mixing the sodium salt and the aluminum salt uniformly in the solution to obtain a mixed solution; The mixed solution is used to perform ion exchange with a cation exchange resin to obtain an aluminum-based adsorption material; The aluminum-based adsorption material is used to treat water, adsorb calcium ions or magnesium ions, form nano-scale aluminum hydroxide precipitates and attach to the aluminum-based adsorption material skeleton, and collect water; Carbon dioxide gas is used to regenerate the aluminum-based adsorption material to dissolve the nano-scale aluminum hydroxide precipitate and replace calcium bicarbonate or magnesium bicarbonate. Water is collected and allowed to stand to form calcium carbonate or magnesium carbonate precipitate.
2. The zero-emission hardness removal process for aluminum-based adsorption materials according to claim 1, characterized in that: In the mixed solution, the mass concentration of sodium salt is 0.002%-0.005%.
3. The zero-emission hardness removal process for aluminum-based adsorption materials according to claim 1, characterized in that: The sodium salt is sodium chloride.
4. The zero-emission hardness removal process for aluminum-based adsorption materials according to claim 1, characterized in that: In the mixed solution, the mass concentration of aluminum salt is 0.1%-3.0%.
5. The zero-emission hardness removal process for aluminum-based adsorption materials according to claim 1, characterized in that: The aluminum salt is aluminum chloride.
6. The zero-emission hardness removal process for aluminum-based adsorption materials according to claim 1, characterized in that: The contact time between the mixed solution and the cation exchange resin is 10 min-15 min.
7. The zero-emission hardness removal process for aluminum-based adsorption materials according to claim 1, characterized in that: The solid-liquid ratio of the cation exchange resin to the mixed solution is 1:50-60.
8. The zero-emission hardness removal process for aluminum-based adsorption materials according to claim 1, characterized in that: The cation exchange resin is a strongly acidic cation exchange resin.
9. The zero-emission hardness removal process for aluminum-based adsorption materials according to claim 1, characterized in that: The particle size of the nano-scale aluminum hydroxide precipitate is 2nm-70nm.
10. The zero-discharge hardness removal process for aluminum-based adsorption materials according to claim 1, characterized in that: The partial pressure of the carbon dioxide is 1.5Kg-10Kg.
Citation Information
Patent Citations
Electric regeneration method for aluminium type hybrid resin
CN101015811A
Methods of utilizing waste waters produced by water purification processing
CN101146438A
Water treatment technology for regenerating filter material by carbon dioxide
CN108928885A
Modified cation exchange resin as well as preparation method and application thereof
CN111892670A
Circulating carbon dioxide regeneration ion exchange system and process for simultaneously realizing water body purification and carbon emission reduction
CN112875803A